Fertility-sparing surgery with neoadjuvant chemotherapy in early and locally advanced cervical cancer: A clinical protocol - Momoko Tanioka; Shoji Nagao; Naoyuki Ida; Yui Tanaka; Atsushi Fujikawa; Ryoko Imatani; Yoshinori Tani; Hanako Sugihara; Kazuhiro Okamoto; Hirofumi Matsuoka; Junko Haraga; Chikako Ogawa; et al. (PLoS ONE, 2026)
Fertility preservation remains a critical concern in young women with early or locally advanced cervical cancer, as standard radical treatments compromise reproductive potential. This study aims to evaluate the feasibility, oncological safety, and reproductive outcomes of fertility-sparing treatment involving neoadjuvant chemotherapy followed by cervical conization and laparoscopic pelvic lymphadenectomy. This single-center, prospective, open-label, single-arm, Phase II interventional study will assess patients with FIGO stage IB2–IB3 cervical cancer (FIGO stage 2018) desiring fertility preservation. Eligible patients will receive three cycles of dose-dense paclitaxel and carboplatin (dd-TC), followed by conization and laparoscopic lymphadenectomy. The primary endpoint is successful uterine preservation. Patients requiring concurrent chemoradiotherapy due to inadequate treatment response will not be considered successful. Secondary endpoints include 2-year recurrence-free survival (RFS), overall survival (OS), quality of life assessments, menstrual and ovulatory resumption, pregnancy, live birth, miscarriage, and preterm birth. Adverse events will be graded according to CTCAE v5.0.